2017
DOI: 10.3390/e19060241
|View full text |Cite
|
Sign up to set email alerts
|

Axiomatic Characterization of the Quantum Relative Entropy and Free Energy

Abstract: Building upon work by Matsumoto, we show that the quantum relative entropy with full-rank second argument is determined by four simple axioms: (i) Continuity in the first argument; (ii) the validity of the data-processing inequality; (iii) additivity under tensor products; and (iv) super-additivity. This observation has immediate implications for quantum thermodynamics, which we discuss. Specifically, we demonstrate that, under reasonable restrictions, the free energy is singled out as a measure of athermality… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
47
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3
1

Relationship

3
6

Authors

Journals

citations
Cited by 55 publications
(54 citation statements)
references
References 30 publications
(41 reference statements)
7
47
0
Order By: Relevance
“…In the first regime, the von Neumann entropy (vNE) or quantities directly related to it prevail, such as the standard quantum relative entropy or mutual information, while in the second regime quantities such as quantum Rényi divergences [8][9][10][11] and smoothed versions of the above [12,13] become important. This common wisdom is, however, recently being challenged [14][15][16][17][18][19], as it has been shown that the vNE determines possible single-shot state transitions in quantum mechanicsunder unitary evolutions -provided that three assumptions hold [18]: i) one can prepare a suitable catalyst, i.e. an auxiliary system that does not change its state during the process but might become correlated with the system on which the transition is performed; ii) one has access to an environment, or source of randomness, that is modelled as a large system in the maximally mixed state; iii) one has full control over system, catalyst and the environment, in the sense that one can implement any unitary on the joint system.…”
mentioning
confidence: 99%
“…In the first regime, the von Neumann entropy (vNE) or quantities directly related to it prevail, such as the standard quantum relative entropy or mutual information, while in the second regime quantities such as quantum Rényi divergences [8][9][10][11] and smoothed versions of the above [12,13] become important. This common wisdom is, however, recently being challenged [14][15][16][17][18][19], as it has been shown that the vNE determines possible single-shot state transitions in quantum mechanicsunder unitary evolutions -provided that three assumptions hold [18]: i) one can prepare a suitable catalyst, i.e. an auxiliary system that does not change its state during the process but might become correlated with the system on which the transition is performed; ii) one has access to an environment, or source of randomness, that is modelled as a large system in the maximally mixed state; iii) one has full control over system, catalyst and the environment, in the sense that one can implement any unitary on the joint system.…”
mentioning
confidence: 99%
“…Notice from the previous definition that the main difference between the relative entropy and D + A,B lies in the fact that the latter lacks the property of monotonicity. Indeed, as mentioned above, since D + A,B verifies the properties of continuity, additivity and superadditivity, we know that it cannot verify the property of monotonicity (i.e., data processing for every quantum channel), as it would imply that it is a multiple of the relative entropy [51]. This motivates the appearance of the property of "semi-monotonicity".…”
Section: Conditional Relative Entropymentioning
confidence: 97%
“…While Definition 2 does not require the catalyst to be uncorrelated with S at the end of the protocol, and in this sense goes beyond the conventional notion of catalysis discussed in the resource-theoretic literature on quantum thermodynamics [6,7], the more general notion of catalysis that we employ here is receiving increasing interest in quantum thermodynamics, where it was shown to single out the quantum relative entropy, free energy and von Neumann entropy [15,8,16], to be useful in the context of algorithmic cooling [16,17] and to show the energetic instability of passive states [18]. Finally, let us briefly comment on the interpretation of the random variable W as work in the setting of β-catalytic channels and the role of the Hamiltonian of the catalyst.…”
Section: Violations Of Nmw and Je Via β-Catalytic Channelsmentioning
confidence: 99%